Identifying and addressing implicature of politicians’ statement on climate change found in Headline news of the Jakarta Post Newspaper - Widya caterine perdhani (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
Abstract. This study uses qualitative content analysis to examine the statements made by politicians in the Jakarta news headline post Jokowi era, and find out the implicature contained in the statements made by politicians on climate change in Indonesia. The study found that the statements made by these politicians had a high level of consideration of the scientific, social and ethical aspects of climate change and there were many implicature contents. Most importantly, the findings show that many statements refer to the discourse of multidisciplinary climate change discourse. Based on the findings, this article shows that the categories of implicatures produced in the headline news corpus data of the Jakarta Post climate change can be developed by adopting guided inquiry.